THE EFFECT OF TEAMWORK, WORK DISCIPLINE AND COMPENSATION ON IMPROVEMENT PTPN III EMPLOYEE PERFORMANCE - Hendra Simanjuntak; Feroaryati Damanik; Johanes Sihombing; Seraphina Lisa Gavrila; Jurisman Simanjorang; Sunday Ade Sitorus; SUNDAY ADE SITORUS (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Data collected from observations at PT. Perkebunan Nusantara III provides credibility to the findings of this research. Teamwork, work discipline, compensation and employee performance are the focus of this study at the PT. This study used qualitative research methods. The findings of this research are based on answers to questions from employees at PT. Perkebunan Nusantara III. The research population consisted of 476 employees from PT. Perkebunan Nusantara III; 72 employees were selected for Validity and Reliability Test. Findings from the Classic Assumption Test, which includes the Normality Test, Multicollinearity Test, and Heteroscedasticity Test, are used to determine the effect of the independent (X) and dependent (Y) tests. This means that the study group was only able to obtain partial results from their 72-item sample with four variables. As a result, the research results are only part of the components of teamwork on employee performance at PT. Perkebunan Nusantara III was partly accepted (Ho) and partly rejected (Ha) according to the value of tcount <ttable or - 0.254<1.995 and significant results 0.800>0.05. Obtaining significant results from 0.000<0.05, the Teamwork component partially obtained a tcount value higher than the ttable value (4.157>1.995).